Food allergies in children – aspects of epidemiology and diet management - Walczak, Marcelina; Grzelak, Teresa; Kramkowska, Marta; Czyżewska, Krystyna (Journal of Medical Science, 2014)
For many years there has been a steady increase in the prevalence of allergic diseases, especially in developed countries. Scientists expect that in the year 2020, atopic diseases will be present in 50% of the population worldwide. Determining the actual scale of the food allergy problem is extremely difficult due to differences in genetic and environmental factors, as well as inconsistent methodology for population and epidemiological research. Treatment of food hypersensitivity is primarily done by excluding a particular food from the diet, while introducing nutritionally equivalent alternatives. An elimination diet should be determined independently for each individual, taking into account the cause, nature, severity and symptoms of the disease. Placing food restrictions on children can interfere with their normal development. The prevailing opinion is that only a properly formulated and followed elimination diet does not endanger the health of the patient. Numerous dietary errors committed, knowingly or unknowingly, by parents can lead to malnutrition and its consequences in their children, such as rickets, anemia, and immune disorders. Therefore, in the long-term treatment of food allergies it is recommended that the caregivers fully cooperate with a doctor, nutritionist and psychotherapist. Due to the ever-increasing incidence of allergic diseases, researchers are looking for effective methods of prevention. Recent scientific reports suggest protective effects from such substances like probiotics, polyunsaturated n-3 fatty acids, vitamin D, antioxidants as well as, certain vegetables and fruits.